Is sharing really caring? Viewpoints on shared decision‐making in paediatrics. (11th February 2020) - Jordan, Zachary; Tremblay, Claire; Lipstein, Ellen; Jordan, Isabel; Boland, Laura
Abstract : Shared decision‐making (SDM), the cornerstone of family‐centred care and the gold standard in health decision‐making, occurs when the patient, family members and the health‐care team members partner to make health decisions about the child. This partnership involves an exchange of medical information and information about patient/family preferences and values. Together, the health‐care team, parent and patient deliberate to determine the best course of action for the child. Despite high‐quality evidence supporting its positive impact on outcomes, SDM has not been widely adopted in paediatric clinical practice. Greater understanding of the impact of SDM on all members of the decision triad (parent, patient and health‐care provider) may increase the likelihood of SDM adoption. Therefore, we present the viewpoints of a paediatric patient, parent and paediatrician about the use of SDM. A youth living with a rare chronic disease discusses the impacts of being involved and excluded from health decisions. A mother of a son living with a rare nephrotic condition discusses working with a health‐care team who are committed and skilled in SDM and the positive impacts SDM has had for her son's care. A general paediatrician with research expertise in SDM discusses the individual and system level challenges and rewards of using SDM in her clinical practice. Based on the viewpoints presented, we offer pragmatic recommendations for using SDM in paediatric clinical practice.